PENGETAHUAN DAN KEPERCAYAAN DIRI SEBAGAI DETERMINAN KEMAMPUAN PERTOLONGAN PERTAMA MASYARAKAT PANTURA TUBAN - Moh. Ubaidillah Faqih; Karyo Karyo; Dwi Kurnia Purnama Sari (Jurnal Keperawatan Malang, 2025)
Background: The high frequency of traffic accidents along the Pantura Tuban corridor underscores the urgent need for community preparedness to act as first responders before professional medical services arrive at the scene. Knowledge and self-confidence are widely recognized as key determinants of the community’s capacity to deliver appropriate first aid. Purpose: This study aimed to examine the relationship between levels of knowledge and self-confidence and the community’s capacity to perform first aid interventions. Methods: This study employed a quantitative approach with a correlational analytic design using a cross-sectional framework. A total of 155 respondents were selected through cluster sampling based on strategic areas along the Pantura corridor. Data were collected using a First Aid Knowledge Questionnaire, a Self-Efficacy Scale in Emergency Response, and an Observation Sheet for First Aid Simulation in Traffic Accident Victims, and were analyzed using the Spearman Rho test. Result: Spearman Rho analysis demonstrated a significant positive correlation between knowledge and first aid ability (r = 0.614; p < 0.001), as well as between self-confidence and first aid ability (r = 0.38; p = 0.01). Implication: Knowledge and self-confidence are primary determinants of community first aid competence. These findings highlight the importance of practice-based training models that integrate both technical and psychological components to develop responsive, resilient, and empowered community emergency preparedness systems. Keywords: community; first aid; knowledge; self-confidence; traffic accident